EVALUATION OF ANTIBACTERIAL AND ANTITUBERCULAR ACTIVITY OF PHASEOLUS VULGARIS LINN., SEEDS - M. R. PRADEEP KUMAR; SHRINIVAS .D. JOSHI; V.H. KULKARNI (International Journal of Pharma and Bio Sciences, 2014)
Due to the increasing emergence of drug resistant Tuberculosis (TB), particularly multi-drug resistant TB (MDR-TB), extensive-drug resistant TB (XDR-TB) and also the development of resistance in the micro-organisms against available drugs there is a need to develop new, potent, fast-acting antibacterial and antitubercular drugs with low toxicity. With this aim different extracts of Phaseolus vulgaris (Linn) seeds were evaluated for antibacterial and antitubercular activities using ciprofloxacin, norfloxacin and isoniazid as standard drugs, respectively. The alcoholic extract showed significant activity against Streptococcus faecalis and Escherichia coli. Petroleum ether extract has shown significant antitubercular activity against M. tuberculosis strain H37Rv and Escherichia coli. The alcoholic and petroleum ether extracts can be considered as a potential candidate for antibacterial and antitubercular activity. The presence of alkaloids in alcoholic extract and steroids, flavonoids in the petroleum ether extract of Phaseolus vulgaris (Linn) seeds could be attributed for the antibacterial and antitubercular activities.